Decreased reward sensitivity in rats from the Fischer344 strain compared to Wistar rats is paralleled by differences in endocannabinoid signaling - Brand, Theresa; Spanagel, Rainer; Schneider, Miriam (PLOS ONE, 2012)
Background The aim of the present study was to examine if differences in the endocannabinoid (ECB) system might be linked to strain specific variations in reward-related behavior in Fischer344 (Fischer) and Wistar rats. Methodology/Principal Findings Two rat strains, the Fischer and the Wistar strain, were tested for different aspects of reward sensitivity for a palatable food reward (sweetened condensed milk, SCM) in a limited-access intake test, a progressive ratio (PR) schedule and the pleasure-attenuated startle (PAS) paradigm. Additionally, basic differences in the ECB system and cannabinoid pharmacology were examined in both rat strains. Fischer rats were found to express lower reward sensitivity towards SCM compared to Wistar rats. These differences were observed for consummatory, motivational and hedonic aspects of the palatable food reward. Western blot analysis for the CB1 receptor and the ECB degrading enzyme fatty acid amide hydrolase (FAAH) revealed a lower expression of both proteins in the hippocampus (HPC) of Fischer rats compared to the Wistar strain. Furthermore, increased cannabinoid-stimulated extracellular-regulated kinase (ERK) phosphorylation was detected in Wistar rats compared to the Fischer strain, indicating alterations in ECB signaling. These findings were further supported by the pharmacological results, where Fischer rats were found to be less sensitive towards the effects of the CB1 receptor antagonist/inverse agonist SR141716 and the cannabinoid agonist WIN 55,212-2. Conclusions/Significance Our present findings indicate differences in the expression of the CB1 receptor and FAAH, as well as the activation of ECB signaling pathways between Fischer and Wistar rats. These basic differences in the ECB system might contribute to the pronounced differences observed in reward sensitivity between both rat strains.
Gesehen am 03.05.2018